1975
DOI: 10.1007/bf02565046
|View full text |Cite
|
Sign up to set email alerts
|

The occurrence of killer character in yeasts of various genera

Abstract: Species of 7 of the 28 yeast genera in the National Collection of Yeast Cultures exhibited killing activity against Saccharomyces cerevisiae. The highest incidence of killer yeasts was found in the genus Hansenula (12 of the 29 strains examined). Saccharomyces, the best represented genus in the Collection, showed a low incidence of killer activity and many of the killer strains are hybrids with a common S. cerevisiae parent. The activities of culture filtrates of the 59 killer yeast isolated responded differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
77
1
1

Year Published

1979
1979
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(83 citation statements)
references
References 9 publications
3
77
1
1
Order By: Relevance
“…Non-Saccharomyces yeasts exhibiting killer activity were first reported by Philliskirk and Young (1975) Wickner (1979) reported that Torulopsis glabrata ATCC15126 also secretes a killer toxin, named K11. Non-Saccharomyces killer toxins originate either from linear dsDNA plasmids or chromosomes (Marquina et al, 2002;Liu et al, 2013), with the notable exception of the killer toxins of H. uvarum and Z. bailii, which originate from virus-like particles (Schmitt & Neuhausen, 1994), similar to those of S. cerevisiae.…”
Section: Killer Toxins Secreted By Non-saccharomyces Yeastsmentioning
confidence: 99%
“…Non-Saccharomyces yeasts exhibiting killer activity were first reported by Philliskirk and Young (1975) Wickner (1979) reported that Torulopsis glabrata ATCC15126 also secretes a killer toxin, named K11. Non-Saccharomyces killer toxins originate either from linear dsDNA plasmids or chromosomes (Marquina et al, 2002;Liu et al, 2013), with the notable exception of the killer toxins of H. uvarum and Z. bailii, which originate from virus-like particles (Schmitt & Neuhausen, 1994), similar to those of S. cerevisiae.…”
Section: Killer Toxins Secreted By Non-saccharomyces Yeastsmentioning
confidence: 99%
“…Killer activity was assayed by the methods described in various earlier papers on the killer phenomenon (8,16). YM agar buffered to pH 4.2 with 0.05 M citrate buffer and containing 0.003% (wt/vol) methylene blue was used as the assay medium.…”
Section: Samples Of Necrotic Opuntia Tissue Yielding Pichia Barkerimentioning
confidence: 99%
“…Killer toxins were first discovered in Saccharomyces cerevisiae by Makower & Bevan (1963) and they have since been found in numerous other yeast genera (Philliskirk & Young, 1975;Stumm et al, 1977;Rosini, 1983Rosini, , 1985Starmer et al, 1987). Through the following years, killer yeasts and their toxins found applications in several fields.…”
Section: Introductionmentioning
confidence: 99%